Profil Peresepan Obat Persalinan Pada Pasien Bedah Sectio Caesarea (SC) Peserta BPJS di Rumah Sakit X Bandung - Daru Imanul Amiq; Rida Emelia (Jurnal Health Sains, 2021)
Sectio Caesarea or Caesarean section is an act of labor to remove the baby through an abdominal or uterine incision. Delivery by cesarean section is intended for absolute or relative indications. Any circumstances that make delivery through the birth canal impossible, is an absolute indication for the abdominal section. This study aims to determine how the profile of prescribing the use of delivery drugs in cesarean section (SC) patients who are BPJS participants at Hospital X Bandung. This study uses descriptive and quantitative methods with secondary data used from prescription sheets and medical record data with a total sample of 58 prescription sheets in the period 5 April to 31 May 202. The results showed that the highest percentage of data was drug therapy Mefenamic Acid (Analgesic) with a dose of 3x500 mg, Tranexamic Acid (Fibrinolytic) with a dose of 3x500 mg, Cefazolin (Antibiotic) with a dose of 1x2 grams, Cefadroxil (Antibiotic) with a dose of 2x500 mg, Fe Tablets (Antianemia) with a dose of 1x300 mg, Ketorolac (Analgesic) with a dose of 3x30 mg, Metoclopramide (Antiemetric) with a dose of 3x10 mg, Oxytocin (Synthetic hormone) with a dose of 1x20 units, Ranitidine (Anti-Selection of Gastric Acid) with a dose of 2x50 mg, and Ringer Lactate (Electrical Fluid) with a dose of 3x500 ml as many as 58 prescription sheets (100%). While the lowest percentage is drug therapy Methyldopa (Antihypertensive) with a dose of 3x500 mg, Nifedipine (Antihypertensive) with a dose of 3x10 mg, MgSO4 20% (Anti-Seizure) with a dose of 1x4 grams and MgSO4 40% (Anti-Seizure) with a dose of 2x500 ml as many as 36 sheets. Prescription (62%). The administration of cesarean delivery drugs was following the dose and did not change the pattern of treatment or use of cesarean delivery drugs at X Hospital Bandung